Influence of storage conditions on the quality of semi‐defatted chia (Salvia hispanica L.) flour. Issue 10 (5th October 2022) - Guiotto, Estefania N.; Nolasco, Susana M.; Tomás, Mabel C.
Abstract: Background: This research evaluates the effects of storage conditions on the quality of the semi‐defatted chia ( Salvia hispanica L.) flour (SDCF), a by‐product from chia seed oil by cold pressing extraction with high nutritional value. For this purpose, SDCF was packaged in different types of packaging materials such as polyethylene (PE), polypropylene (PP), metalized biaxially oriented polypropylene films (BOPP), and triple kraft (K) and stored at 4 ± 1 and 20 ± 2°C for 240 days. Moisture content, fatty acids composition by GC, tocopherol content by HPLC, total phenolic content (TPC), and 2, 2‐diphenyl‐1‐picrylhydrazyl (DPPH) radical scavenging activity assays by spectrophotometry were determined. Oxidative stability was monitored by peroxide values (PV), induction time (Rancimat), and free fatty acids content (FFA). Results: Moisture content was below 9% during storage, and the fatty acids profile was stable under different storage conditions. The TPC and DPPH radical scavenging activity, γ‐ and δ‐ tocopherol contents decreased significantly ( p  < 0.05) with storage time; PV were lower than 10 meq O2 /Kg oil under the studied parameters and the oxidative stability showed the highest level at 4 ± 1°C. The FFA content was <2% at 4 ± 1°C, overpassing this level after 120 days at 20 ± 2°C. SDCF showed a low microbial activity, which could be due to tocopherols and phenolic compounds. Conclusions: Temperature and storage time had a significant influence on the quality of SDCF being BOPP packaging at 4 ± 1°C is the most effective method for their preservation from deteriorative processes.